Digital crisis management: how proactive online engagements on patient complaints influence social media users’ perceptions - Sang Lee; Samar Ben Romdhane (Frontiers in Communication)
This study investigates how a pharmaceutical company’s responses to patients’ complaints regarding side effects affect social media users’ evaluation of a paracrisis situation. An online study was conducted by simulating a real-world paracrisis situation in which patients petitioned about the serious side effects of a drug on the pharmaceutical company’s Facebook page. Results showed that users who are actively engaged with social media reacted more positively when the pharmaceutical company proactively responded to a paracrisis situation. In particular, user engagement moderated the effects of company engagement on perceived crisis likelihood. In turn, perceived crisis likelihood mediated the interaction effects on users’ intention to spread negative eWOM and purchase intentions. Thus, this study highlights the importance of proactive engagement by demonstrating the mitigating effects of precrisis engagement when an organization faces a potential crisis situation on social media. It adds theoretical implications to crisis communication literature and provides practical implications as to how online negative events might be managed to minimize negative consequences.